Reliability-based design optimization of structural systems under hybrid probabilistic and interval model. (November 2015) - Xia, Baizhan; Lü, Hui; Yu, Dejie; Jiang, Chao
Highlights: HPRMM is proposed to estimate the objective function. HPIMM is proposed to evaluate the component reliability. RBDO based on HPRMM and HPIMM is developed. Effectiveness of RBDO based on HPRMM and HPIMM are investigated. Abstract: Reliability-based design optimization (RBDO) under hybrid probabilistic and interval model is a nested loop optimization whose computational cost rising from evaluation of the objective function and the component reliability is considerable. To improve its computational efficiency, a hybrid perturbation random moment method (HPRMM) to estimate the objective function and a hybrid perturbation inverse mapping method (HPIMM) to evaluate the component reliability will be proposed. Based on HPRMM and HPIMM, the nested loop optimization is converted into an efficient single-loop process. Effectiveness and efficiency of proposed approaches are checked by solving optimization problems of a structural–acoustic system and a disc brake system.